Socio-Religious Implications of the Teachings of Buddhist Kosāmbiya Sutta: An Exploration - Hasan, Md Rakibul (Philosophy and Progress, 2025)
Buddhism presents teachings that emphasize a doctrine of non-violence, promoting peace, solidarity, unity, and cooperation. Gautama Buddha, the founder of Buddhism, has consistently advocated for the alleviation of human suffering and the attainment of liberation from it. Attaining liberation is the ultimate goal of Buddha’s teachings. The Kosāmbiya Sutta’s substance, together with the concept of suffering and the methods for its alleviation, is examined within the framework of the social and religious setting of the Buddha’s teachings and philosophy. To achieve relief and a harmonious conclusion, the Buddha underscores the significance of embracing and implementing Loving Kindness, Dāna, Sīla, and Right View as articulated in the Kosāmbiya Sutta, which is analyzed and implicated in this study within both religious and societal frameworks. Furthermore, research has elucidated how the correct perspective, as the ultimate abode, operates from an elevated standpoint within Buddhist philosophy, encompassing concepts such as solidarity, unity, and the Seven Factors outlined in this sutta, which are notably efficacious in achieving sotāpatti (stream-entry) and conducive to attaining nirvāna. This study employs a qualitative methodology driven by the Theravāda Buddhist Tripitaka. This study aims to analytically present the relevance, compatibility, and need of the Buddha’s teachings within a social context. This is a humble contribution to the interpretation of Buddha’s teachings, acting as a guiding light for fostering societal unity, solidarity, and peace. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 253-277